PERSEPSI MAHASISWA JURUSAN ADMINISTRASI PUBLIK DAN BISNIS TERHADAP PELAKSANAAN E-LEARNING - Hutauruk, Rosinta (Jurnal Komputer dan Teknologi, 2024)
This research was conducted with the aim of finding out the perceptions of students majoring in Business Administration and majoring in Public Administration at the University of Indonesia Mandiri in using e-learning facilities which include student enthusiasm when learning, the advantages and disadvantages of e-learning, and student expectations regarding e-learning. The design of this research is descriptive qualitative research where the researcher distributes questionnaires, where the research subjects are public administration and business administration students who are taking Industrial and Organizational Psychology (IOP) courses. The research results show that students, both working and non-working, are enthusiastic about using e-learning because learning is done online. Initial introduction to the e-learning platform helps students follow e-learning courses. The process of learning and collecting assignments using e-learning apparently saves time and costs and speeds up students in completing assignments and exams in PIO courses. Internet access apparently is not a problem in taking e-learning lectures. Students feel that the schedule used in providing materials or assignments is scheduled so that students can manage their study and work schedules.